Hak dan kewajiban menurut UUD 1945 bagi warga negara indonesia: Hak dan kewajiban sebagai warga negara republik indonesia - IRFANI, MUHAMMAD YAZID (Maliki Interdisciplinary Journal, 2025)
The rights and obligations of citizens are fundamental pillars in establishing a harmonious national life. Rights such as the right to work, express opinions, and access education must be guaranteed by the state, while obligations like obeying the law, maintaining public order, and participating in national defense must be carried out responsibly. The legal basis for these aspects is enshrined in Articles 27 to 34 of the 1945 Constitution of the Republic of Indonesia. However, in practice, there remains a disparity between the fulfillment of citizens' rights and the performance of their duties. Addressing this imbalance requires a collective commitment from the government, legal institutions, social organizations, and the general public. Fair law enforcement, strengthening non-political institutions, improving public service quality, and raising civic awareness through education are strategic efforts to achieve a comprehensive balance between rights and responsibilities. Achieving this balance is expected to foster a just, orderly, and prosperous social order.